Metal Allergy - V. K. Kapitanova; N. E. Petrova; M. Yu. Zhdanova; L. V. Nevskaya (Биопрепараты: Профилактика, диагностика, лечение, 2019)
Allergic reactions associated with sensitisation to metals are a common but underexplored problem. Due to the frequent use of metals and their alloys there has been an increase in the number of registered cases of allergic reactions. Recently there have been cases when allergic reactions were induced by metals that were previously considered absolutely inert and non-allergenic, such as gold, palladium and others. The aim of this work was to summarise scientific data on allergic reactions to metals and their diagnosis in humans. In medicine, alloys of nickel, palladium and gold are used in the manufacture of both surgical instruments and various implants used in orthopedics, endovascular surgery, gynecology and dentistry. Allergic reactions to these metals may lead to failure of artificial joints, thrombosis of endovascular stents, stomatitis, gingivitis, and dermatitis. The most frequent allergic reaction to metals is contact dermatitis which is most frequently caused by nickel. Metal allergies are diagnosed by skin tests. There are no Russian-made diagnostic systems for detecting metal allergies. The diagnosis of allergic contact dermatitis is performed with the help of AllerTest test kit («TRUE Test», Denmark). Therefore, elaboration of a domestic diagnostic test for timely detection of allergies to metals is still relevant.